2018
DOI: 10.1680/jgein.17.00034
|View full text |Cite
|
Sign up to set email alerts
|

Methodology to evaluate hydraulic compatibility of geotextile and RCA in underdrain systems

Abstract: Long-term filtration tests were conducted to assess the hydraulic compatibility of the recycled concrete aggregate (RCA) and nonwoven geotextile that is typically used in underdrains. The RCA samples used in this study were collected from a single facility, but with different ages (aged in the laboratory). Geotextile samples were also exhumed after each test and evaluated for reduction in their serviceability. The laboratory tests showed that aging does not adversely affect the hydraulic properties of the RCA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…The results of these tests are shown in Table 4. The results of the tests were evaluated, based on the system permeability as defined in the literature ( 21 ), as the overall permeability within the test set-up. The system permeability is dictated by the lowest permeability of the material within the system.…”
Section: Results Of Hydraulic Conductivity Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of these tests are shown in Table 4. The results of the tests were evaluated, based on the system permeability as defined in the literature ( 21 ), as the overall permeability within the test set-up. The system permeability is dictated by the lowest permeability of the material within the system.…”
Section: Results Of Hydraulic Conductivity Testsmentioning
confidence: 99%
“…The experiments were performed with hydraulic gradient of 1 (the gradient was gradually increased from 0.25 to 0.5 to 0.75 to 1), which covers the worst-case scenario in pavement applications ( 20 ). The results of the tests were evaluated in accordance with the interpretations described in literature ( 21 ).…”
Section: Methodology Used In This Study To Evaluate Exhumed Samplesmentioning
confidence: 99%
“…RCA-geotekstil sisteminin filtrasyon performansının, doğal agrega-geotekstil sisteminin filtrasyon performansından farklı olduğunu belirtmişlerdir. RCA'daki yaşlanmanın filtrasyon performansını etkilediğini belirtmişlerdir [37]. Ryoo ve Aydilek (2019) üç farklı kompost malzeme ve farklı gözenek açıklıklarına sahip üç örgülü geotekstil ile iki örgüsüz geotekstilin filtrasyon performansını değerlendirmek için laboratuvarda uzun süreli filtrasyon deneyleri yapmışlardır [38].…”
Section: Introductionunclassified
“…4 The clogging of the geotextiles consists of physical clogging, 5,6 chemical clogging 7 and biological clogging, 8 and the chemical clogging is more complex than the physical clogging. 9 Researchers have done a great deal of work on the chemical clogging of geotextiles. [10][11][12] McIsaac and Rowe 13 simulated a typical leachate collection system in a landfill using a mesocosm setup, which showed that the nonwoven geotextile had higher resistivity to chemical clogging than the woven geotextile.…”
mentioning
confidence: 99%